1993
DOI: 10.1016/0928-8244(93)90069-g
|View full text |Cite
|
Sign up to set email alerts
|

Pili and the interaction of Aeromonas species with humanperipheral blood polymorphonuclear cells

Abstract: The interaction of differentially piliated Aeromonas strains expressing pili of two broadly different morphologic types (short, rigid (S/R) and/or long, wavy (L/W)) with human peripheral blood mononuclear leukocytes (PMN) was investigated to determine whether host defense cells might exert a selective pressure on pili expression in vivo accounting for the different pili phenotypes of clinical and environmental strains. A majority of Aeromonas veronii biotype sobria strains from water (6/6) and faeces (8/11) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Carbohydrate-reactive OMPs (CROMPS), which may be porins for fucose, have also been postulated as adhesins and may be intestinal adhesive factors [27,28], but do not appear to mediate binding to cell lines. The A. hydrophila strain (strain A6) from which these OMPs were purified was not adhesive in the above cell line assays [3,16]. Indeed, we have found that most A. hydrophila strains, even those isolated from diarrhoeal faeces as sole potential pathogen (eg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbohydrate-reactive OMPs (CROMPS), which may be porins for fucose, have also been postulated as adhesins and may be intestinal adhesive factors [27,28], but do not appear to mediate binding to cell lines. The A. hydrophila strain (strain A6) from which these OMPs were purified was not adhesive in the above cell line assays [3,16]. Indeed, we have found that most A. hydrophila strains, even those isolated from diarrhoeal faeces as sole potential pathogen (eg.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria and preparations of filamentous structures obtained from bacterial strains by mechanical shearing were examined under a Philips 410 electron microscope at 80 kV following staining with uranyl acetate (1 %) for 30 s to 1 min as described elsewhere [16].…”
Section: Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental strains of A. veronii biovar sobria are generally more heavily piliated that fecal isolates (23,24). There is some evidence that Bfp promote binding to phagocytic cells, which may represent a selective pressure resulting in a shift in the degree of piliation in vivo (19).…”
Section: Discussionmentioning
confidence: 99%